Isolation and clinical sample typing of human leptospirosis cases in Argentina - Chiani, Yosena (2016)
Fil: Chiani, Yosena. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Respiratorias; Argentina.